Memory’s Seams: Scarcity and Preciousness in Earth Pigments - Eugenia Kisin (Museum & Society)
A naturally occurring carbon-based ‘mineral black’ mined from ancient flood seams in North Devon, England, Bideford black embodies the contradictions of modernity, and how it is felt at social and bodily scales. During the Second World War, the material was mined for its coal-like properties to conceal tanks and ships, while its intense color and oily texture coated eyelashes in Max Factor’s first commercial mascara until it was replaced by blacker polymers—an ambivalent form of synthetic mimicry and that displaces mining by way of plastics. More recently, artists and community stakeholders working in Devon have reanimated the natural pigment as an important piece of biocultural heritage. This object biography tells the story of Bideford black and its parallel transformations of extraction, from the exploitation of a finite resource to its displacement by synthetics, whose ‘toxic progenies’ (Davis 2022) make different kinds of claims on the future.